A Low‐Cost Polyaniline@Textile‐Based Multifunctional Sensor for Simultaneously Detecting Tactile and Olfactory Stimuli. Issue 12 (7th October 2018) - Tang, Xing; Wu, Congyi; Zhang, Tian; Zhou, Tingting; Wang, Hao; Xie, Changsheng; Zeng, Dawen
Abstract: Multifunctional sensors are those able to respond to both physical and chemical stimuli and potentially capable of differentiating two or more signals. However, a low‐cost multifunctional sensor able to distinguish different signals is hard to fabricate. Here, a low‐cost polyaniline@textile‐based multimodal sensor is demonstrated to be able to simultaneously detect and distinguish tactile and olfactory stimuli in a single pixel. The multifunctional sensor has a high pressure sensitivity over a wide range of pressures (300 Pa–30 kPa) and an excellent linear response to NH3 at room temperature. More importantly, it can differentiate different stimuli due to different mechanisms for pressure sensing and gas sensing. With its low cost and multiple functionality, the sensor is promising for practical applications in wearable electronics and human health monitoring. Abstract : Compared with the previous multifunctional sensor, the PANI@textile‐based multifunctional sensor is able to respond to both physical and chemical stimuli. The sensor can differentiate different stimuli due to different mechanisms for pressure sensing and gas sensing. The sensor is promising for practical applications in wearable electronics and human health monitoring.